Physical perfection and tempering as a constituent of introduction of Cossack pedagogics in patriotic education of border students-guards. - Miroshnichenko Valentina Ivanovna; Stavickiy Oleg Nikolaevich (Kharkov National Pedagogical University, 2011)
Purpose of the article is study of features value of physical perfection and tempering as a constituent of introduction of Cossack pedagogics in patriotic education of border students-guards. Material for writing of the article was experience of lead through of the noted measures in terms an academy. As a result of creative introduction in the conditions of educational-educate future border officers-guards acquire the process of higher military educational establishment of Cossack traditions and consuetude physical health, moral cleanness and spiritual wealth, develop patriotic qualities.